A catalyst for education? A study on the impact of artificial intelligence assisted learning in painting courses on college students' continuous learning intention - Jie Sun; Xinyi Huang; Xin Sun; Qianling Jiang; Chun Yang; Wei Wei; Wei Miao; Chao Gu (Acta Psychologica, 2025)
This study examines artificial intelligence in college students' painting education and their potential impact on students' continuous learning intention. In this study, two surveys were conducted. The first survey included 793 valid samples, and the second survey contained 210 valid samples. Study 1 established the path influence relationship between self-perceived creativity, flow experience, learning interest, and continuous learning intention, confirming gender and educational level as moderators. Study 2 identifies 4 positive factors and 3 negative factors to continuous learning intention through exploratory factor analysis. These findings not only provide a reference for the application of artificial intelligence to art education, but also provide new ideas and approaches for the widespread promotion and application of artificial intelligence to other disciplines of education.